2021
DOI: 10.1017/s1742170520000411
|View full text |Cite
|
Sign up to set email alerts
|

Precision planting impacts on winter cereal rye growth, nutrient uptake, spring soil temperature and adoption cost

Abstract: Growing winter cereal rye (Secale cereale) (WCR) has been identified as an effective in-field practice to reduce nitrate-N and phosphorus (P) losses to Upper Mississippi River Basin, USA. In the Midwestern USA, growers are reluctant to plant WCR especially prior to corn (Zea mays L.) due to N immobilization and establishment issues. Precision planting of WCR or ‘skipping the corn row’ (STCR) can minimize some issues associated with WCR ahead of corn while reducing cover crop seed costs. The objective of this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…Cereal cover crops have been shown to be effective in reducing weed biomass, but growers are concerned that cover crops could reduce the tiller density and biomass production of the cash crops as well [47,48]. Sadeghpour et al reported rye is an excellent crop to control weeds, but found lower switchgrass tiller density in rye but improved switchgrass tiller density with oat, in line with findings of this study [28].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Cereal cover crops have been shown to be effective in reducing weed biomass, but growers are concerned that cover crops could reduce the tiller density and biomass production of the cash crops as well [47,48]. Sadeghpour et al reported rye is an excellent crop to control weeds, but found lower switchgrass tiller density in rye but improved switchgrass tiller density with oat, in line with findings of this study [28].…”
Section: Discussionsupporting
confidence: 85%
“…Previous research in Massachusetts indicated that oat, when planted early, is able to accumulate a great amount of biomass [19] and, when terminated by frost, can cover the soil but does not induce immobilization; therefore, it allows the cash crop to be established. Over-wintering cover crops such as rye and wheat, if not terminated early (this was the case in our study), can severely tie up N, use water and reduce the cash crop's establishment and production [47][48][49][50]. These reasons explain the differences between oat and rye in improving switchgrass tiller density.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The partial budget analysis confirmed that by excluding yield penalty for corn after WCR from the production costs, double cropping WCR with corn is feasible in four out of five site-years even at hay price as low as $110 Mg −1 . Improved agronomic management practices such as precision planting of WCR (skipping the corn rows) are capable of minimizing the negative effect of WCR on the following corn crop yield (Sadeghpour et al, 2021). Eliminating the cost of nutrient removal (typical in concentrated dairy farms with excess nutrients) made WCR forage production feasible at all site-years at a hay price of ≥$110 Mg −1 .…”
Section: Discussionmentioning
confidence: 99%
“…One major component of agronomic management for WCR forage production is harvest date because dry matter (DM) yield and quality rapidly changes in the spring. Previous reports show that WCR can produce 2-4 Mg DM ha −1 in the Northeast and Midwest United States when harvested at the boot stage (Kantar et al, 2011;Ketterings et al, 2015;Sadeghpour et al, 2021). However, when the date of harvest is delayed from boot stage to soft dough stage, a 30-60% yield increase in winter cereals DM yield is expected (Collar & Askland, 2001;Helsel & Thomas, 1987;Edmisten et al, 1998;Lyon et al, 2001).…”
mentioning
confidence: 99%